Travel‐Related Leptospirosis: A Series of 15 Imported Cases. Issue 4 (15th May 2013) - van de Werve, Charlotte; Perignon, Alice; Jauréguiberry, Stéphane; Bricaire, François; Bourhy, Pascal; Caumes, Eric
Abstract: Background: Leptospirosis belongs to the spectrum of travel‐related infections. Methods: We retrospectively studied all the consecutive cases of travel‐related leptospirosis seen in our department between January 2008 and September 2011. Patients were included with a clinical picture compatible with the disease within 21 days after return, the presence of a thermoresistant antigen or IgM antibodies, Elisa ≥ 1 /400, and a positive microagglutination test (MAT) ≥ 1/100. Results: Fifteen leptospirosis cases were evaluated. Exposure occurred in Asia (47%), Africa (20%), the Caribbean (20%), and Indian Ocean (13%). Fourteen patients were infected during water‐related activities. On admission the most frequent symptoms were fever (100%), headache (80%), and digestive disorders (67%). Relevant laboratory findings included impaired liver function tests (100%), lymphocytopenia (80%), thrombocytopenia (67%), and elevated C‐reactive protein (CRP) (67%). Our cases were confirmed by MAT that found antibodies against nine different serovars. Seven patients were cured with amoxicillin, four with doxycycline, two with ceftriaxone, one with ceftriaxone, doxycycline, and spiramycin, whereas one recovered spontaneously (retrospective diagnosis). Eight patients were hospitalized. All patients recovered. Conclusion: Our cases involved nine different serovars. They were related to travel in Asia, Africa, and the Caribbean. Bathing or other fresh‐water leisure activities (canoeing, kayaking, rafting) are the most likely at‐risk exposure. Any traveler with fever and at‐risk exposure should be investigated for leptospirosis.